Effects of maternal cold exposure and nutrient restriction on the ghrelin receptor, the GH-IGF axis, and metabolic regulation in the postnatal ovine liver - Melanie Healy (Reproduction, 2008)
Maternal cold exposure of pregnant sheep promotes fetal growth, whereas nutrient restriction (NR) can reverse this effect. The present study was designed to establish whether cold exposure induced by winter shearing of the mother at 70 days gestation (term=147 days), with or without NR (induced by a 50% reduction in maternal food intake from 110 days gestation), has specific effects on mRNA abundance of hepatic genes related to growth and liver energy metabolism that could regulate postnatal body and liver growth. Measurements of hepatic gene expression for the GH secretagog receptor-1a (GHSR-1A), peroxisome proliferator-activated receptor (PPAR)alpha, phosphoenolpyruvate carboxykinase (PEPCK), and glucose-6-phosphatase activity together with glycogen content were made in the livers of offspring at 1 and 30 days of age. Maternal NR reduced liver mass at day 1, whereas offspring of cold-exposed mothers had larger livers at day 30 irrespective of maternal diet. Cold exposure resulted in the up-regulation of GHSR-1A mRNA abundance and reduced glucose-6-phosphatase activity at 1, but not 30 days of age, whereas IGF-II mRNA was decreased at 1 and 30 days. PPARalpha mRNA abundance was enhanced, while PEPCK was reduced in 30-day old offspring of cold-exposed mothers. NR caused reductions in IGF-I mRNA and, at 1-day postnatal age, down-regulated GHR, while, at 30 days, reduced GHSR-1A gene expression and hepatic glycogen content. In conclusion, we have shown that maternal cold exposure and NR have different effects on the hepatic GH-IGF and metabolic axis that may contribute to changes in liver growth over the first month of life.